1993
DOI: 10.1007/bf00838440
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar encephalitis in adults

Abstract: We examined 11 adult patients with cerebellar encephalitis (CE) during the acute phase of the disease and at least 12 months later. Five patients were aged between 23 and 31 years, 3 patients between 43 and 44 years and 3 patients between 60 and 64 years. Serological tests gave evidence of Epstein-Barr virus infection in 4 of the 5 young patients. Two patients had serological evidence of varicella-zoster virus reactivation, whereas the serological findings were negative in all other cases. All patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
6

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 24 publications
1
40
0
6
Order By: Relevance
“…Em relatos iniciais, anticorpos contra EBV 12 , linfócitos com EBV ou linfócitos atípicos foram encontrados no líquor de pacientes com encefalite aguda por mononucleose sugerindo uma invasão direta do vírus no sistema nervoso central 8 . Contudo, outros estudos não encontraram anticorpos ou partículas virais no líquor, o que pode sugerir um mecanismo imunológico como causa da inflamação cerebelar 13 .…”
Section: Discussionunclassified
“…Em relatos iniciais, anticorpos contra EBV 12 , linfócitos com EBV ou linfócitos atípicos foram encontrados no líquor de pacientes com encefalite aguda por mononucleose sugerindo uma invasão direta do vírus no sistema nervoso central 8 . Contudo, outros estudos não encontraram anticorpos ou partículas virais no líquor, o que pode sugerir um mecanismo imunológico como causa da inflamação cerebelar 13 .…”
Section: Discussionunclassified
“…Cerebellar encephalitis is reported both in elderly and non-elderly patients. However, dissimilar from outcome of younger patients, the disease may lead to a persistent and more severe cerebellar ataxia (Klockgether et al, 1993).…”
Section: Prognosismentioning
confidence: 95%
“…MRI lesions in the cerebellar white matter suggested that the demyelinating process is related to an autoimmune mechanism [8,9]. Klockgether et al [10] reported a clinical follow-up study of adults with cerebellar encephalitis. Some of the patients, who were older than 60 years at disease onset, had persistent cerebellar ataxia, and MRI revealed infratentorial atrophy [10].…”
Section: Discussionmentioning
confidence: 99%
“…Klockgether et al [10] reported a clinical follow-up study of adults with cerebellar encephalitis. Some of the patients, who were older than 60 years at disease onset, had persistent cerebellar ataxia, and MRI revealed infratentorial atrophy [10]. In our patient, there was recovery from cerebellar signs 8 months after disease onset, and MRI without shrinkage of the cerebellum or brain stem was observed.…”
Section: Discussionmentioning
confidence: 99%